Encouraging the participation of children and young people to develop research: a qualitative study in a rare childhood disorder. (24th May 2012) - Tibbins, C; Callens, C; Lim, MJ; Wassmer, E; Cummins, C; Absoud, M
Abstract : Aims: Multiple Sclerosis (MS) is the most common disease causing neurological disability in young adults but is rare in children. MS causes slow neurodegeneration with relapses (attacks) and remission (partial recovery) and is treated with injectables. Adult studies of new oral drugs show 50% greater efficacy compared to current treatments but are more cytotoxic. The European Medical Agency requires a paediatric investigation plan (PIP) for testing of all new drugs in children. The aim of this qualitative study was to elicit opinions from a wide range of young people and families on developing research and clinical trials for children with MS. Methods: A qualitative focus group methodology was employed in 3 different phases: 1) in a school setting with research naive young people (n=56) 2) with young people (n=12) who were research savvy and had knowledge of long term chronic conditions 3) with research naive young people with MS (n=9) and their guardians. Groups were presented with key information about clinical research and background to proposed trials as in the PIPs. Explicit questions were asked of the groups to elicit discussions and feedback. Consultations were recorded, transcribed and analysed using Nvivo analysis software to identify emergent themes. Results: Themes identified were: – children/young people's altruism; – young people believe medicines need to be tested in children; – explaining processes of clinical trials, especially randomisation is difficult and requires time; – families distaste to the concept of computer randomisation; – the negative impact of the media regarding randomised controlled trials (RCTs); – importance of considering safety especially in younger children; – the negative connotation of the word trial compared to a safety study; – the paramount importance of understanding side effects of treatments on children; – the importance of children's maturity to comprehend complexities of trial participation; – the trepidation of children to having injections; – the reassurance of knowing others are involved in the same trial. Conclusions: The results from this study illustrate the importance of allowing the participation of children early in clinical trial design to understand their views and ensure study feasibility and success.